Urgensi KPEI Dalam Sistem Perdagangan Saham Tanpa Warkat Di Bursa Efek - Tiana, Fasya Putri; Pramudita, Rendi; Julita, Priscilla Nanda (Jurnal Ekonomika Dan Bisnis (JEBS), 2023)
With the skyrocketing advances in technology, this also has an impact on the economic sector, including the capital market sector. Technological developments in the capital sector have made stock trading which was originally carried out manually with stock certificates, now turning more practical with the term scriptless trading or scriptless. And even in practice, this scripless sale and purchase of shares is supported by the LKP (Clearing Guarantee Institution) conducted by PT. KPEI (Indonesian Clearing and Underwriters). This implementation is in accordance with the provisions stipulated in Law No. 8 of 1995 in Article 55 paragraph 1. Where this law regulates the capital market as a manifestation of the mandate for the development of scripless stock trading.